Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Rumah Makan Sambel Layah Cabang Kendal - Widodo Wibisono; Mohammad Hidayatul Holili (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of service quality on customer satisfaction at the Sambel Layah Restaurant, Kendal Branch. The data collection technique used a questionnaire instrument with 105 respondents, then collected and checked for validity and then presented in an informative and scientific manner. After that the data is processed in a comprehensive and descriptive-analytic manner. Then the data is tested with SEM (Structural Equation Model) statistics to determine the relationship between various variables. The results of the study stated that the hypothesis which said that Service Quality had a positive effect on Customer Satisfaction was proven significantly. This can be seen in table 5. where the service quality variable indicators for all indicators show a calculated t value that is greater than t table. t table 1.658 while t count average 3.276 which means that service quality has a positive and significant effect on customer satisfaction